The Transformation of Kading Village: Development Strategies Based on Local Potentialand Community Participation - Ismail, Ismail; Siraj, Muhammad Luthfi (Program Pascasarjana Universitas Negeri Makassar, 2025)
This study aims to analyze development strategies based on local potential and community participation in Kading Village. This study uses a qualitative descriptive approach with a purposive sampling technique to identify key informants capable of providing in-depth information regarding social phenomena and village development. Data collection was conducted through observation, interviews, and documentation, while data analysis followed the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing/verification. The research results show that Kading Village possesses diverse local potential, including natural resources, human resources, social assets, and cultural heritage. However, asset mapping remains administrative in nature and does not optimally involve community participation, resulting in underutilization of economic and social potential. The local economic sector is dominated by traditional agriculture and livestock, with low-value-added home-based business initiatives. Village economic independence is suboptimal due to dependence on external assistance, and the role of Village-Owned Enterprises (BUMDes) has not fully promoted community productivity. Local innovation is also limited to traditional practices and the adoption of simple technologies, while community participation in development planning, monitoring, and evaluation remains symbolic. This research emphasizes the need for a development strategy based on participatory mapping of local assets, strengthening economic institutional capacity, and local innovation involving collaboration between the government, community, academics, and the private sector. Through a participatory approach and community empowerment, Kading Village has the potential to achieve inclusive, sustainable, and locally potential-based development